2011
DOI: 10.1136/thoraxjnl-2011-200251
|View full text |Cite
|
Sign up to set email alerts
|

What makes for an effective stop-smoking service?

Abstract: Background The English network of stop-smoking services (SSSs) is among the best-value life-preserving clinical intervention in the UK NHS and is internationally renowned. However, success varies considerably across services, making it important to examine the factors that influence their effectiveness. Methods Data from 126 890 treatment episodes in 24 SSSs in 2009e10 were used to assess the association between intervention characteristics and success rates, adjusting for key smoker characteristics. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 5 publications
5
109
1
2
Order By: Relevance
“…There was no evidence of differential effects by gender as found in previous studies [16,17]. As in previous findings on effectiveness [31] and efficacy [32], pharmacotherapy use in this clinic mostly predicted higher abstinence than no medication. This included the antidepressant bupropion for which a recent Cochrane review found only weak evidence of efficacy in smokers with past depression and no clear evidence in smokers with current depression [33].…”
Section: Discussionsupporting
confidence: 58%
“…There was no evidence of differential effects by gender as found in previous studies [16,17]. As in previous findings on effectiveness [31] and efficacy [32], pharmacotherapy use in this clinic mostly predicted higher abstinence than no medication. This included the antidepressant bupropion for which a recent Cochrane review found only weak evidence of efficacy in smokers with past depression and no clear evidence in smokers with current depression [33].…”
Section: Discussionsupporting
confidence: 58%
“…Smokers frequently attempt quitting several times unsuccessfully before achieving long-term abstinence (9,10). Smokers who seek support in quitting are much more likely to quit than those who try to quit alone, and the most effective aid for achieving smoking cessation is medication (e.g., nicotine replacement therapy, or varenicline) coupled with tailored behavioral support from specialist stop smoking services, like the National Health Service Stop Smoking Services (NHS SSS) in the UK (11)(12)(13).…”
mentioning
confidence: 99%
“…On the basis of these associations, other direct evidence on the effectiveness of particular techniques (e.g. [24,25]), and PRIME theory, a core set of BCTs was selected by the study team and linked together in a variety of ways consistent with their use in the evidence-based and successful NHS Stop Smoking Services. This approach is based on an expert Stop Smoking Advisor being both a ready source of information that smokers trying to stop may want or need, and a guide to help the smoker through the process of stopping, using a structured quit plan.…”
Section: Methodsmentioning
confidence: 99%